DESIGNING RURAL TOUR PROGRAM IN CONNECTING TOURISM VILLAGE TO RESORT TOURISTS, TANJUNG LESUNG, BANTEN INDONESIA - Agoes, Adrian; Edison, Emron; Kemala, Zia (ITB Journal Publisher, LPPM ITB, 2019)
One model in developing a tourism village is to institute a connection with other more established attractions. This research is to find out whether this strategy can be applied to develop tourism in Cikadu hamlet by initiating a connection with a more established resort nearby. The method used in this research is a qualitative approach. The data were collected through observations and interviews with key informants. General Manager of the resorts, tourism activists of the hamlet, and government staffs in the village were interviewed to look into the problems. Historically, there were a number of tourists already directed by Tanjung Lesung Resorts to have a trip to Cikadu hamlet. The model of connecting a more established resort to help develop tourism in a nearby hamlet has shown some results. Tourists who stayed at the resort had come to the hamlet for certain periods to make an alternative trip in enriching their holiday. However, it appeared that the hamlet wasn?t ready enough to host tourists from the resorts for the lack of tourism competencies of human resources. Most of the tourism executors in the hamlet were farmers, so the experience design was not optimal. The handling of the tour programs was considered un-proficient for the resort?s guests. The model of establishing connection to resort tourists in developing tourism in Cikadu can actually be achieved. Albeit, designing a more appropriate tour program is essential to keep the tourists visit continually.